¿Qué seguridad para Africa? : tres imágenes del kaleidoscopio africano - Zorgbibe, Charles (Estudios Internacionales, 1983)
In this paper, three images of the African kaleidoscope are presented, three aspects of its diplomatic and strategic system. In short, three possible ways to explore the means and objectives of an "African security". The first image is classic: a diplomacy that does not take place throughout the continent, but in different “sub-regions”. The second is futuristic: to respond to Africa's ambition to secure its domestic politics and to participate in world politics, there is a nuclear-armed nonalignment. The third image is more current: the strategic position of Africa is not comparable to the limited military power of the African states, a disadvantage of technological underdevelopment. But there is also the internal vulnerability of poorly consolidated political regimes, of nations deeply divided into rival ethnic groups, and external interference as a result of East-West tensions.